Disentangling the effect of waiting times on hospital choice: Evidence from a panel data analysis - Matteo Lippi Bruni; Cristina Ugolini; Rossella Verzulli (Alma Mater Studiorum - Università di Bologna, Dipartimento di Scienze Economiche (DSE), 2018)
This study examines the effect of waiting times on hospital choice by using patientlevel data on elective Percutaneous Transluminal Coronary Angioplasty (PTCA) procedures in the Italian NHS over the years 2008-2011. We perform a multinomial logit analysis including conditional logit and mixed logit specifications. Our findings show the importance of jointly controlling for time-invariant and time varying dimensions of hospital quality in order to disentangle the effect of waiting times on hospital choice. We provide evidence that patients are responsive to changes in waiting times and aspects of clinical quality within hospitals over time, and estimate the trade-off that patients make between different hospital attributes. The results convey important policy implications for highly regulated health care markets.
Keywords: I10; 330; hospital choice; waiting times; hospital quality; multinomial logit models